World Development Report 1994 : Infrastructure for Development - World Bank (New York: Oxford University Press, 2012)
World Development Report 1994, the seventeenth in this annual series, examines the link between infrastructure and development and explores ways in which developing countries can improve both the provision and the quality of infrastructure services. In recent decades, developing countries have made substantial investments in infrastructure, achieving dramatic gains for households and producers by expanding their access to services such as safe water, sanitation, electric power, telecommunications, and transport. Even more infrastructure investment and expansion are needed in order to extend the reach of services - especially to people living in rural areas and to the poor. But as this report shows, the quantity of investment cannot be the exclusive focus of policy. Improving the quality of infrastructure service also is vital. Both quantity and quality improvements are essential to modernize and diversify production, help countries compete internationally, and accommodate rapid urbanization. The report identifies the basic cause of poor past performance as inadequate institutional incentives for improving the provision of infrastructure. To promote more efficient and responsive service delivery, incentives need to be changed through commercial management, competition, and user involvement. Several trends are helping to improve the performance of infrastructure. First, innovation in technology and in the regulatory management of markets makes more diversity possible in the supply of services. Second, an evaluation of the role of government is leading to a shift from direct government provision of services to increasing private sector provision and recent experience in many countries with public-private partnerships is highlighting new ways to increase efficiency and expand services. Third, increased concern about social and environmental sustainability has heightened public interest in infrastructure design and performance. This report includes the World Development Indicators, which offer selected social and economic statistics for 132 countries.